Effect of Delayed Stimulation of Sigma-1 Receptor on Embolic Model of Cerebral Ischemia in Rat - M Allahtavakoli (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: It has been reported that selective sigma receptor agonists have neuroprotective properties in permanent or transient models of middle cerebral artery (MCA) occlusion. Neuroprotective effects of sigma receptor agonists in the embolic model of stroke have not yet been reported which were investigated in the current study.METHODS: In this experiment, 24 male Wistar rats (250-300 gr) were randomly categorized to 3 groups including control, treatment and sham. Embolic ischemia was induced by injection of 20 mm (5 µl) natural clot into MCA and in sham-operated animals 5 µl saline was injected. Animals then were treated with the sigma-1 receptor agonist PRE-084 (10mg/kg i.p) vehicle (saline) 3h and 24h after stroke. Infarct volume and neurological deficits were conducted at 48h after stroke induction and compared.FINDINGS: Infarct volume in PRE-084 treated or control groups were 11.8±1.65 and 26.45±2.19, respectively (p<0.001). Treatment with PRE-084 also improved neurologic motor and sensory behaviours (p<0.001).CONCLUSION: The findings of the present study suggest the neuroprotective effects of sigma-1 receptor agonists in the embolic model of stroke, which is very resemble to ischemic stroke in clinic.